Diagnostic and prognostic impact of cardiac magnetic resonance, including scar quantification and strain imaging in patients with malignant ventricular arrhythmias and nonobstructed coronary arteries. (8th February 2021) - Szabo, L; Bodi, V; Czimbalmos, CS; Dohy, ZS; Horvath, V; Toth, A; Suhai, FI; Geller, L; Becker, D; Merkely, B; Vago, H
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Development and Innovation Fund of Hungary, National Research, Development and Innovation Office Background: In case of malignant ventricular arrhythmias (VA) and nonobstructed coronary arteries, the differential diagnosis of the underlying diseases is still challenging, due to the board spectrum of possible causes. Cardiac magnetic resonance (CMR) provides functional, morphological and tissue specific information, including necrotic and scar-tissue. Aims: We aimed to assess the diagnostic and prognostic implications of CMR parameters including global strain values and myocardial scar in patients after ventricular fibrillation (VF) or sustained ventricular tachycardia (SVT) and nonobstructed coronary arteries. Methods: Between 2011 and 2019, 99 patients (42 ±17 years, 54 male) presenting with VF or SVT and nonobstructed coronary arteries, who underwent CMR examination before secondary prevention implantable cardioverter defibrillator (ICD) implantation were included in our study. Post-processing included feature-tracking strain analysis and left ventricular (LV) scar quantification. Patients were followed for the combined endpoint of all-cause-mortality and appropriate ICD therapy. Results: CMR examination proved structural myocardial disease in 72%: dilated (n = 21), arrhythmogenic (n = 11), hypertrophic cardiomyopathy (n = 7) and other cardiomyopathies (n = 3). We found LGE patterns showing chronic myocardial infarction (n = 4), suggesting chronic myocarditis (n = 4) and aspecific nonischemic scar formation (n = 14). In 7 cases aspecific structural alterations without scar formation were detected. Overall, myocardial scar was found in 52%, with an average extent of 12 ± 8% of the LV myocardium. The CMR examination changed the clinical diagnosis in 55% of the patients. During a median follow-up at 2 years, 6 patients died and 42 experienced appropriate ICD therapy. We found an association between cardiac events and the presence of structural abnormality and myocardial scar (logrank: 4, 553, p < 0.05 and 8.375, p <0.01). On Cox proportional-hazards modell LV ejection fraction, LV stroke volume index, the presence of structural abnormality, the presence and extent of myocardial scar, global LV strain parameters including longitudinal and circumferential strain, and a global left ventricular dssynchrony parameter (mechanical dispersion) were univariate predictors of the combined endpoint of all-cause-mortality and appropriate ICD therapy(p < 0.05). Conclusion: CMR performed in patients after malignant VA and nonobstructed coronary arteries not only establishes the diagnosis in a high proportion of patients, but may also provide additional prognostic factors. This may indicate that CMR could play a complementary role in the risk stratification in this patient population.